(untitled) (De Legibus - Law Journal, 2021)
The text critically analyzes the evolution, in the portuguese legalsystem, of the clauses of value used for the qualiﬁcation of the thef crime, reachingthe conclusion that the model currently adopted implies some diﬃculties towardsthe principle of legal reserve in criminal matters.